Faktor-Faktor Yang Mempengaruhi Efektivitas Implementasi Program AML/CFT: Kompetensi SDM, Infrastruktur Teknologi, Dan Komitmen Manajemen - Muhidin, Adam Desvian; Kuntadi, Cris (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Prior research plays a crucial role in reinforcing theoretical frameworks and elucidating relationships among variables in scientific inquiry. This article reviews the determinants influencing the effectiveness of Anti-Money Laundering and Countering the Financing of Terrorism (AML/CFT) program implementation, focusing on human resource (HR) competency, technology infrastructure, and management commitment within Category 1 Payment Service Providers (PJP) in Indonesia. Category 1 PJP, as regulated under Bank Indonesia Regulation No. 23/6/PBI/2021, includes entities offering comprehensive payment services such as account issuance, payment initiation, acquiring, account information services, and remittances, including e-wallets and payment gateways. The primary objective of this study is to formulate hypotheses regarding the relationships among these variables for subsequent empirical testing. Employing a qualitative library research methodology, this study draws upon books and peer-reviewed journals sourced from Mendeley, Google Scholar, and other academic databases. The literature review identifies a substantial research gap, as 73.3% of prior studies adopt qualitative-normative approaches, with limited quantitative empirical evidence integrating HR, technological, and managerial factors in the Indonesian payment services sector. The findings suggest that HR competency, technology infrastructure, and management commitment each exert a positive influence on the effectiveness of AML/CFT program implementation, thereby providing a theoretical basis for future quantitative, survey-based research